Stability of freeze-dried vaginal Lactobacillus strains in the presence of different lyoprotectors - Juárez Tomás, María Silvina (2009)
The industrial use of lactic acid bacteria as probiotic cultures depends on the preservation techniques employed, which are required to guarantee stable cultures in terms of viability and functional activity. The aim of this study was to evaluate the effects of 12% lactose and 12% sucrose suspended in water or reconstituted skim milk on the survival and expression of beneficial characteristics during freeze-drying and subsequent storage of 6 vaginal lactobacilli strains. A cubic polynomial model was also used for the first time to evaluate the effects of different protectors on survival behavior during storage. Different survival patterns were observed among the strains considered. The presence of both lactose and sucrose in water or in 6% skim milk as the suspension medium proved to be effective in maintaining a high degree of survival and expression of potentially probiotic characteristics (production of antimicrobial substances or auto-aggregation capabilities) of most strains after lyophilization and long-term storage. This study constitutes a valuable step to obtain concentrated cultures with the highest stability of microorganisms for pharmaceutical purposes.